Lymph node metastasis in suprasternal space and intra-infrahyoid strap muscle space from papillary thyroid carcinoma - Qianqian Yuan (Journal of Otolaryngology - Head and Neck Surgery, 2020)
Abstract Background This study was performed to evaluate the clinicopathologic characteristics of Lymph Node metastasis between investing layer of Cervical fascia and deep fascia of infrahyoid strap Muscles (LNCM) in papillary thyroid carcinoma (PTC). Methods Retrospective review of patients with PTC who underwent thyroidectomy and central compartment neck dissection (CND) from January 2016 to January 2018 was performed in two tertiary referral academic medical centers. A total of 2104 consecutive patients with PTC who underwent thyroidectomy and CND were included in the retrospective review. The LNCM was resected as a separate specimen by the surgeon and the clinicopathologic characteristics of the patients were recorded. Multivariate logistic regression analysis was performed to identify risk factors for LNCM metastasis. Results Of 2104 PTC patients, 451 patients (21.4%) had lymph nodes in the LNCM. Among them, 68 (15.1%) cases were confirmed to be positive in the LNCM. In total, the metastasis rate of LNCM in PTC patients was 3.2% (68/2104). Univariate analysis revealed that the metastasis of LNCM were more likely to have a primary site in the inferior pole, extrathyroidal extension (ETE), central cervical metastasis, level III and level IV metastasis. Multivariate analysis further showed tumor location in the inferior pole, ETE, level III and level IV metastasis conferred a significantly increased odds ratio for LNCM metastasis. Conclusion Attention should be paid to the lymph tissue in the LNCM for PTC patients, especially in presence of a primary site in the inferior pole, ETE, level III and level IV metastasis.